THE IMPORTANCE OF QUALITY EDUCATION IN OUR LIVES - Shuhratova, Khadicha; Khan, Tatyana (Инновационные исследования в современном мире: теория и практика, 2023)
Illiteracy has always been a global concern and this paper focuses on the role of education in people's lives. The importance of education, especially a tertiary one is explained. This research however is aimed to show the importance of producing quality graduates and the ways to raise educational standards. Furthermore, the negative consequences of low standards, and how the issue was formulated with relevant qualifications thus making these graduates employable and most suitable for the job.